2005
DOI: 10.1111/j.1460-9568.2005.04114.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and spatial learning in goldfish is dependent on different telencephalic pallial systems

Abstract: In mammals, the amygdala and the hippocampus are involved in different aspects of learning. Whereas the amygdala complex is involved in emotional learning, the hippocampus plays a critical role in spatial and contextual learning. In fish, it has been suggested that the medial and lateral region of the telencephalic pallia might be the homologous neural structure to the mammalian amygdala and hippocampus, respectively. Although there is evidence of the implication of medial and lateral pallium in several learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 54 publications
(99 reference statements)
6
78
0
1
Order By: Relevance
“…Rose (2002Rose ( , 2007 and Cabanac et al (2009), argue that Table 1 Examples of behavioural changes in responses to aquaculture procedures or stressors that could be used as species-specific operational welfare indicators in farmed fish Beaumont et al (1996) Juvenile lake chubsuckers Erimyzon sucetta Scheduled (vs. on demand): : swimming speed and turning angles Noble et al (2007b, c) this is not possible because their behaviour is simple and reflexive and they lack a neocortex. Yet, a growing body of evidence related to cognitive (Braithwaite 2006), neuroanatomic (Portavella and Vargas 2005;Rodriguez et al 2006) and emotional (Sneddon 2007;Yue et al 2008) aspects of fish behaviour provides strong support for sentience (the ability to feel) in fish. Good welfare should therefore be related to behaviours associated with attraction and positive anticipation and reward behaviour, while bad welfare should be associated with frustration, aversion, fear, pain and sickness behaviours.…”
Section: Mental States and Possible Associated Welfare Indicatorsmentioning
confidence: 99%
“…Rose (2002Rose ( , 2007 and Cabanac et al (2009), argue that Table 1 Examples of behavioural changes in responses to aquaculture procedures or stressors that could be used as species-specific operational welfare indicators in farmed fish Beaumont et al (1996) Juvenile lake chubsuckers Erimyzon sucetta Scheduled (vs. on demand): : swimming speed and turning angles Noble et al (2007b, c) this is not possible because their behaviour is simple and reflexive and they lack a neocortex. Yet, a growing body of evidence related to cognitive (Braithwaite 2006), neuroanatomic (Portavella and Vargas 2005;Rodriguez et al 2006) and emotional (Sneddon 2007;Yue et al 2008) aspects of fish behaviour provides strong support for sentience (the ability to feel) in fish. Good welfare should therefore be related to behaviours associated with attraction and positive anticipation and reward behaviour, while bad welfare should be associated with frustration, aversion, fear, pain and sickness behaviours.…”
Section: Mental States and Possible Associated Welfare Indicatorsmentioning
confidence: 99%
“…In teleost fish, the dorsolateral telencephalon (DL) participates in spatial orientation and learning, and it is probably homologous to the mammalian hippocampus [23,24], a cell proliferation zone in mammals that is influenced by predator stimuli [9,25]. The dorsomedial telencephalon (DM), a likely homologue of the mammalian amygdala, is involved in conditioned avoidance [24,26], and the ventral telencephalon (V), a likely homologue of basal ganglia, is involved in selecting motor actions and evaluating their outcome [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the absence of effects on spatial memory or motor response (Portavella & Vargas, 2005) rules out a possible functional homology with the hippocampus and basal ganglia of tetrapods (Braford, 1995;Braford et al, 1992;Echteler & Saidel, 1981;Murakami et al, 1983;Nieuwenhuys & Verrijdt, 1983;Northcutt, 1995;Northcutt & Braford, 1980;Parent, 1986;Parent et al, 1978). Thus, we concluded that the lesion produced a deficit in the associative process between the discriminative stimulus and the shock (Portavella et al, 2002;2004a, 2004bPortavella & Vargas, 2005;Vargas et al, 2009). Other results in fear context conditioning have showed that lesions of the dorsomedial telencephalic portion in Betta splendens produced a facilitation of habituation to the context (Marino-Neto & Sabbatini, 1983) and variations in levels of aggression (de Bruin, 1980).…”
Section: Function Of the Amygdala Homologous In Non Mammals Vertebratesmentioning
confidence: 84%
“…These studies showed a clear lesion effect in both the acquisition and maintenance of a two-way active avoidance behavior (Portavella et al, 2004a(Portavella et al, , 2004bPortavella & Vargas, 2005). Thus, lesions to the Dmv region produce a deficit equivalent to those described in the case of complete ablation of the telencephalon in earlier studies in Pavlovian conditioning (Aronson, 1948;de Bruin, 1977;Fiedler, 1967;Hale, 1956;Kamrin & Aronson, 1954;Karamyan et al, 1967;Kassel & Davis, 1977;Kassel et al, 1976;Noble, 1939;Noble & Bourne, 1941;Overmier & Gross, 1974;;Segaar, 1961;Segaar & Nieuwenhuys, 1963;Ribbink, 1972).…”
Section: Function Of the Amygdala Homologous In Non Mammals Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation